Services potential in the Caribbean. - FRECKLETON, Marie (1996)
Argues that Caribbean countries need to develop new exports, and the potential for the development of services in the region is quite good. The services with the most potential appear to be tourism, data processing and banking and insurance. Identifies major obstacles as (a) shortage of funds to upgrade the physical infrastructure and to invest in the development of human resources; (b) weak regulatory capacity of some governments; (c) environmental degradation; and (d) inefficient production patterns.